1988
DOI: 10.1029/ja093ia11p12783
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional magnetosheath plasma ion distributions from 200 eV to 2 MeV

Abstract: We present initial measurements of the three‐dimensional magnetosheath plasma ion flow and spectrum over the energy range of 200 eV to 2 MeV. These observations are from two magnetosheath traversals, one each on the dawn (December 19, 1977) and dusk (July 7, 1978) flanks of the magnetosphere. Data are from three‐dimensional plasma and energetic ion observations from the ISEE 1 satellite. The data show the continuous presence of a high‐energy (≳5 keV) tail in the magnetosheath ion population during these two tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 21 publications
2
18
0
Order By: Relevance
“…From these spectra we conclude that a lowenergy ion population was escaping at those times, upstream from the bow shock, under a variety of IMF directions and bow shock structures. Since the E $6 keV ion population was highly anisotropic along the IMF (data not shown in the ®gure) and not dependent on the IMF direction/bow shock structure, we infer that this is more consistent with leakage of magnetosheath superthermal ions from an ion source downstream of the bow shock whose density is independent of the angle h B n (Tanaka et al, 1983;Williams et al, 1988), than with bow shock acceleration (Ipavich et al, 1988). We point out that ®eld aligned beams of higher energy (³50 keV) ions were observed at the onset of all the three November 1, 1984, upstream events of Figs.…”
Section: The November 1 1984 Ion Eventsmentioning
confidence: 61%
See 1 more Smart Citation
“…From these spectra we conclude that a lowenergy ion population was escaping at those times, upstream from the bow shock, under a variety of IMF directions and bow shock structures. Since the E $6 keV ion population was highly anisotropic along the IMF (data not shown in the ®gure) and not dependent on the IMF direction/bow shock structure, we infer that this is more consistent with leakage of magnetosheath superthermal ions from an ion source downstream of the bow shock whose density is independent of the angle h B n (Tanaka et al, 1983;Williams et al, 1988), than with bow shock acceleration (Ipavich et al, 1988). We point out that ®eld aligned beams of higher energy (³50 keV) ions were observed at the onset of all the three November 1, 1984, upstream events of Figs.…”
Section: The November 1 1984 Ion Eventsmentioning
confidence: 61%
“…The terrestrial magnetosphere has been known for many years to be an important source of energetic (³30 keV) ions in the magnetosheath (Williams et al, 1988;Kudela et al, 1992;Paschalidis et al, 1994;Karanikola et al, 1999) and the near Earth interplanetary space (Sarris et al, 1978;Anagnostopoulos et al, 1986;. It is also known that dierent estimations for the extent of contribution of the magnetospheric ion population in the magnetosheath and the upstream region have been postulated Anagnostopoulos et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…For the magnetosheath (the worst case) we used the measured ion fluxes from the CODIF instrument on the Cluster mission for our analysis (shown in Fig. 7), which are similar to magnetosheath measurements reported earlier (Williams et al 1988;Paschalidis et al 1994). Table 2 shows the background fluxes on the conversion surface or conversion foil for the IBEX energy steps under these assumptions and using the cross sections of H + on water (Greenwood et al 2000).…”
Section: Local Ion Populationsmentioning
confidence: 95%
“…In addition, the plasma sheet population of energetic particles alone suces to warrant the lower observable¯uxes in magnetosheath. The density gradient of energetic particles is directed toward the magnetopause (Williams et al, 1988;Traver et al, 1991;Paschalidis et al, 1994;Eastman and Christon, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Williams (1979) presented strong evidence for signi®cant but sporadic magnetosheath energy¯ow in the antisolar direction using 50± 220 keV ions. Williams et al (1988) studied two magnetosheath traversals, one on each of the dawn and dusk anks of the magnetosphere. They concluded that the magnetosheath plasma often has at least two major components, the shocked solar wind seen at energies £5 keV (which behaves independently of the magnetic ®eld direction) and the magnetospheric (plasma sheet) particles seen at energies ³5 keV (which are highly modulated by the magnetic ®eld).…”
Section: Introductionmentioning
confidence: 99%